Economic policy : a European Forum (Oxford Blackwell Publishers, 1998)
Economic Policy provides timely and authoritative analyses of the choices confronting policymakers. The subject matter ranges from the study of how individual markets can and should work to the broadest interactions in the world economy.
Economic policy is published twice a year in April and Oct.
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC POLICY; ECONOMIC RECESSION